ANALISIS BELANJA TIDAK LANGSUNG KABUPATEN/KOTA DI PROPINSI JAMBI TAHUN 2009-2014 - Mila Permata Sari (Jurnal Manajemen Terapan dan Keuangan, 2020)
This study aims to identify and analyze the development of indirect spending in districts / cities in Jambi Province in 2009-2014. In addition, it is also used to determine and analyze the efficiency of indirect spending in terms of district / municipal efficiency in Jambi Province 2009-2014. The technical analysis used is qualitative and quantitative analysis, analysis of expenditure allocation on indirect spending development, analysis of spending performance in terms of efficiency. The development of district / municipal indirect spending in Jambi province in 2009-2014 was based on the annual average, namely the highest in Bungo district at 1.19% and the lowest in Tanjung Jabung Timur district at 0.11%. Based on the efficiency of district / municipal indirect spending in Jambi province in 2009-2014, the average target indirect expenditure from year to year has increased because from 2009-2014 all districts have been efficient from year to year in managing indirect expenditure. Districts / Cities in Jambi Province in Sungai Penuh City have been very effective from the efficiency of indirect spending.